Упростите выражение:

а) (x+4)2-7x ;

б) (c-1)2-(1-2c);

в) (x-y)2+(y-x);

г) (a+b)2-2b(a-b) ;

д) 9m2-(n-3m)2;

е) (a2+b2)-(a-b)2;

ж) z(5-z)+(z-5)2;

з) 3u(u+2)-(u+3)2.

2

Ответы и объяснения

2013-03-10T22:36:12+04:00

а)=2х+8-7x=-5х+8

б)=2c-2-1+2с=4с-3

в)=2x-2у+у-x=x-y

г)=2а+2b-2ab+2b^2

д)=9m^2-2n+6m

е)=а^2+b^2-2a+2b

ж)=5z-z^2+2z-10=-z^2+7z-10

з)=3u^2+6u-2u-6=3u^2+4u-6

 

2013-03-10T22:52:03+04:00

а) (x+4)2-7x ;

х2+2*х*4+42 -7х= х2 +8х+16-7х= х2+х+16

б) (c-1)2-(1-2c);

с2-2*с*1+12 -1+2с= с2-2с+2с= с2

в) (x-y)2+(y-x);

х2-2ху+ у2+у-х= х2+ у2 -2ху+у-х

г) (a+b)2-2b(a-b) ;

а2+2аb+ b2-2ab+2 b2= a2+ b2+2ab

д) 9m2-(n-3m)2;

9 m2-n2-2*n*3m+9m2=-n 2-6nm

е) (a2+b2)-(a-b)2;

a2+b 2-a 2 -2ab-b 2=-2ab

ж) z(5-z)+(z-5)2;

5z-z 2  +z 2 -2*z*5+5 2=5z-10z+25=-5z+25=-z+5

з) 3u(u+2)-(u+3)2.

3u2+6u-u2-2*u*3-32=2u 2 -9